2015
DOI: 10.1016/j.redox.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal iron supplementation potentiates oxidative stress, energetic dysfunction and neurodegeneration in the R6/2 mouse model of Huntington's disease

Abstract: Huntington’s disease (HD) is a progressive neurodegenerative disorder caused by a CAG repeat expansion that encodes a polyglutamine tract in huntingtin (htt) protein. Dysregulation of brain iron homeostasis, oxidative stress and neurodegeneration are consistent features of the HD phenotype. Therefore, environmental factors that exacerbate oxidative stress and iron dysregulation may potentiate HD. Iron supplementation in the human population is common during infant and adult-life stages. In this study, iron sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 48 publications
9
45
0
Order By: Relevance
“…2). This finding corroborates our prior study demonstrating that neonatal, but not adult, iron supplementation potentiates disease in the rapidly progressive R6/2 mouse HD model [16]. The studies support work investigating if iron supplementation in HTT mutation positive infants has a role in potentiating the human disease.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…2). This finding corroborates our prior study demonstrating that neonatal, but not adult, iron supplementation potentiates disease in the rapidly progressive R6/2 mouse HD model [16]. The studies support work investigating if iron supplementation in HTT mutation positive infants has a role in potentiating the human disease.…”
Section: Discussionsupporting
confidence: 91%
“…Significantly increased body weights in HD mice from 3 months of age (not shown) complicates interpretation of these data. In contrast to the neonatal iron study, and in agreement with our prior study in R6/2 HD mice [16], we found no evidence that increased iron intake in adult-life potentiates HD (Figs. 5–7).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations